2015
DOI: 10.1371/journal.pone.0133894
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Expression Profile Reveals Potential Biomarkers and Therapeutic Targets in Canine Endometrial Lesions

Abstract: Cystic endometrial hyperplasia (CEH), mucometra, and pyometra are common uterine diseases in intact dogs, with pyometra being a life threatening disease. This study aimed to determine the gene expression profile of these lesions and potential biomarkers for closed-cervix pyometra, the most severe condition. Total RNA was extracted from 69 fresh endometrium samples collected from 21 healthy female dogs during diestrus, 16 CEH, 15 mucometra and 17 pyometra (eight open and nine closed-cervixes). Global gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 26 publications
0
33
0
1
Order By: Relevance
“…could also been detected [11,22,23] . It has been established that if E. coli migrates to the uterus, it binds with higher affinity to the endometrium and myometrium layers and constitutes a resistance to the uterus' defense mechanisms such as lactoferrin and mucin-1 [24][25][26][27] . As reported in previous studies [4,11,23,28] , gram negative bacteria (75%) such as E. coli, Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%
“…could also been detected [11,22,23] . It has been established that if E. coli migrates to the uterus, it binds with higher affinity to the endometrium and myometrium layers and constitutes a resistance to the uterus' defense mechanisms such as lactoferrin and mucin-1 [24][25][26][27] . As reported in previous studies [4,11,23,28] , gram negative bacteria (75%) such as E. coli, Klebsiella spp.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, new omics technologies and rapid sequencing methods have been developed, which has prompted possibilities for new studies. One study of gene activation identified 29 genes that are upregulated during the disease (Voorwald et al., ). Importantly, products of the upregulated genes are possible diagnostic indicators for use in clinical practice if rapid and cost‐effective diagnostic tests are developed (Bukowska et al., ; Chu Py, Salamonsen, Lee, & Wright, ; Hagman, Rönnberg, & Pejler, ; Silva et al., ).…”
Section: What Is New About Diagnosis and Treatment Of Pyometra?mentioning
confidence: 99%
“…Immune system of reproductive organs of animals is represented by a number of cellular and humoral protective factors. Recently, scientists from different countries of the world are increasingly attracted by the role of immune cells in the formation of immune homeostasis in the body of animals (Hagman et al, 2009;Sheldon et al, 2010;Voorward et al, 2015). After all, Immune responses are important at all stages of the formation of the reproductive system of animals and have a regulating effect in different periods of their reproductive ability (Silva et al, 2012;Amos et al, 2014;Wira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%